Range management and cows’ consumption of Trichloris crinita - Klich M.G. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Continuous use of the livestock fields in the middle valley of the river Negro, Northern Patagonia, Argentina is causing rangeland degradaion. Cattle breeding using rotation regimes between plots of known vegetation composition in a valley field, with 303 mm historical annual rainfall, was planned to evaluate the population of Trichloris crinita, a native to the Americas known by the common name False Rhodes Grass, and to estimate its consumption and preference by cows. To describe the floristic composition, identification of the plant species was undertaken on point intercepting lines. The diet of the grazing animals was determined by microhistological studies using epidermal characteristics to identify the plant components in fecal samples of cows. Plots at the lower edge of the plateau that surrounds the valley, with alluvial soils and little biodiversity, where T. crinita grows spontaneously, were left free from animals during the summer and autumn, allowing vegetative and reproductive development of the plant species. The use of this forage in winter as deferred pasture permitted the increase of the T. crinita population with higher annual dry matter production per plant, and it resulted in enhanced cow consumption.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)